2017
DOI: 10.1186/s12880-017-0214-8
|View full text |Cite
|
Sign up to set email alerts
|

The value of ultrasound-guided biopsy of fluorodeoxy-glucose positron emission tomography (FDG-PET)-positive supraclavicular lymph nodes in patients with suspected lung cancer

Abstract: BackgroundAccurate lymph node staging is essential for adequate prognostication and therapy planning in patients with non-small cell lung cancer (NSCLC). FDG-PET/CT is a sensitive tool for the detection of metastases, including non-palpable supraclavicular lymph node (SCLN) metastases. Histological proof of metastatic spread and mutation analysis is crucial for optimal staging and therapy. The aim of this study was to investigate the value of ultrasound-guided fine needle aspiration cytology (FNAC) and core bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The authors reported an SUV max of 2.3 to be the optimum cut-off for differentiating true-and false-positive findings. A smaller study of 12 patients with lung cancer and FDG-avid cervical lymphadenopathy showed supraclavicular metastases from lung cancer in 10 cases; 1 case showed evidence of sarcoidosis and another evidence of metastatic breast cancer [14]. Mean SUV max in Two cases of lymphoma on cytology were later confirmed on surgical excisional biopsy.…”
Section: Discussionmentioning
confidence: 96%
“…The authors reported an SUV max of 2.3 to be the optimum cut-off for differentiating true-and false-positive findings. A smaller study of 12 patients with lung cancer and FDG-avid cervical lymphadenopathy showed supraclavicular metastases from lung cancer in 10 cases; 1 case showed evidence of sarcoidosis and another evidence of metastatic breast cancer [14]. Mean SUV max in Two cases of lymphoma on cytology were later confirmed on surgical excisional biopsy.…”
Section: Discussionmentioning
confidence: 96%
“…The use of PET scan may help identify the active disease from collapsed normal lung tissue or benign lesions, or may detect more accessible lesion that was not described with other imaging modalities (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 Histological diagnosis of lung cancer is very important for optimal staging and therapy, sampling for which is often obtained under image guidance. 4 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Histological diagnosis of lung cancer is very important for optimal staging and therapy, sampling for which is often obtained under image guidance. 4 Percutaneous lung biopsies have one of the highest complication rates of all imaging-guided biopsy procedures. 5,6 Sampling from supraclavicular lymph nodes, if possible, can avoid such complications but still provide us with the histological diagnosis, as even small non-palpable supraclavicular lymph nodes can Free Full Text Articles are Available at www.jnma.com.np harbour metastases.…”
Section: Introductionmentioning
confidence: 99%